Zastosowanie rozszerzonego współczynnika Giniego jako miernika ryzyka do wyznaczania portfela akcji - Gluzicka, Agata (Application of the Extended Gini's Mean as a Risk Measure in Determining a Shares Portfolio, 2007)
In the traditional Markowitz's approach to determining optimal portfolio, a variance (or the standard deviation) is being accepted as the measure of risk. Beside the variance, there exist many different quantities which are applied as the risk measures. One of such measures was proposed by Yitzhaki, who used Gini's mean difference as a risk measure. Yitzhaki is also the author of the model, in which the risk is measured by the so-called extended Gini's mean. This coefficient is a modification of the Gini's mean difference, which considers the level of risk aversion. In this paper the author will show more significant properties of the extended Gini's mean. This measure will be applied in determining optimal portfolios for companies listed on the Warsaw Stock Exchange.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 75-83